Kinematic modeling of dike deformation near the Husavik-Flatey fault, Flateyjarskagi, Iceland - Betke-Brunswick, Lillian Naomi (Carleton Digital Commons, 2011)
The Husavik-Flatey fault is a dextral transform fault between the Kolbeinsey ridge and the North Iceland Volcanic Zone, two segments of the Mid-Atlantic Ridge. The Husavik-Flatey fault is exposed above sea level on Iceland, providing a unique opportunity to study the geologic structures developed along an oceanic transform fault. On Flateyjarskagi, a peninsula in northern Iceland, basaltic dikes show a 110° change in orientation with distance from the Husavik-Flatey fault. I assume heterogeneous simple shear and construct seven two-dimensional kinematic models of deformation of these dikes. Using different decreasing functions for Î³(y) to describe the orientation of dikes with distance from the Husavik-Flatey fault, I compare how accurately these functions predict dike orientations near the ridge-transform intersection. I then use the models to calculate an average shear strain of 0.7 and estimate 21 km of displacement along the Husavik-Flatey fault.